Virusna okužba, celično posredovan imunski odziv in genomski učinki vitamina D - Lojk, Jasna (Laboratorijska medicina, 2021)
An adequate and timely immune response is essential for the protection from pathogens, including viruses. This involves several different immune cell types, which exert their specific roles in different stages of the infection: pathogen recognition and antigen processing, recruitment of immune cells to the site of infection, presentation of antigens and activation of the adaptive immune response through activation of B and T lymphocytes, production of antibodies and establishment of the immunological memory. Each step is highly regulated through cellular communication and several positive and negative feedback loops. Vitamin D plays a crucial part in this, since its main role is in regulation of the intensity and duration of the immune response through stimulation of regulatory T cells, which prevent excessive activation of the immune system and thus negative consequences for the organism.
Keywords: COVID-19; Imunski odziv; Koronavirusi; SARS-CoV-2; Virusi; Vitamin D